(untitled) (London Journal of Research In Management & Business, 2025)
The development model implemented in Guayana, based on industrialization and the exploitation of natural resources, has entered a deep crisis. Changes in the economic and political context, along with the implementation of new strategies such as the Orinoco Mining Arc, have generated a series of social and environmental problems that require urgent attention. In light of these issues and the absence of official data reflecting the well-being or distress of the inhabitants of Bolvar state, a study on well-being in the region was conducted from a local perspective, considering inequalities and living conditions of the population. This project adopts an approach that integrates individuals’ material living conditions and their satisfaction with those conditions in order to calculate the well-being index. The objective is to share information that can guide the design of public policies that address the real needs of Bolvar states society. The inclusion of a subjective dimension in the applied survey allowed the results to reflect the necessity of recognizing that each individual values quality of life from their own perspective and that their individual capacities and opportunities influence their perceptions. The study aims to further explore disparities among the inhabitants by incorporating analyses of territorial, age, and gender inequalities. This study underscores the need for a more comprehensive and human-centered approach to regional development that considers the needs and aspirations of the local population.